2018
DOI: 10.4025/actascibiolsci.v40i1.37844
|View full text |Cite
|
Sign up to set email alerts
|

<b>Toxicity of the goji berry fruit associated with artificial excipients and dried without additives

Abstract: The aim of this study was to evaluate the cytotoxic and genotoxic potential of goji berry fruit-based pharmaceutical powders obtained from three pharmaceutical laboratories. The product A was tested at concentrations of 0.012; 0.025 and 0.05 g mL-1 , and B and C at concentrations 0.02; 0.04 and 0.08 g mL-1. It was also evaluated the tea of the dried goji berry fruit (non-additives) in the concentrations 0.035; 0.07 and 0.14 g mL-1 for comparison to the results obtained with powdered goji berry. Tea concentrati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 29 publications
(36 reference statements)
0
1
0
Order By: Relevance
“…Preservatives, dyes, flavors, sweeteners, thickeners, emulsifiers, and stabilizers are commonly used in pharmaceutical laboratories (Balbani et al, 2006). Moura et al (2018) used the root meristem of Alliym cepa L. (onion) as an efficient bioassay for the initial screening of the genetic toxicity. They found that industrialized goji berries at all concentrations, including those indicated for use by pharmaceutical companies, had significant potential for toxicity.…”
Section: In the Pharmaceutical Industrymentioning
confidence: 99%
“…Preservatives, dyes, flavors, sweeteners, thickeners, emulsifiers, and stabilizers are commonly used in pharmaceutical laboratories (Balbani et al, 2006). Moura et al (2018) used the root meristem of Alliym cepa L. (onion) as an efficient bioassay for the initial screening of the genetic toxicity. They found that industrialized goji berries at all concentrations, including those indicated for use by pharmaceutical companies, had significant potential for toxicity.…”
Section: In the Pharmaceutical Industrymentioning
confidence: 99%